Catechol biosensing using a nanostructured layer-by-layer film containing Cl-catechol 1,2-dioxygenase - Zucolotto, V; Pinto, APA; Tumolo, T.; Moraes, M. L.; Baptista, M. S.; Riul, A.; Araujo, APU; Oliveira, O. N. (Elsevier B.V., 2006)
dThe detection of aromatic compounds from pesticides and industrial wastewater has become of great interest, since these compounds withstand chemical oxidation and biological degradation, accumulating in the environment. In this work, a highly sensitive biosensor for detecting catechol was obtained with the immobilization of Cl-catechol 1,2-dioxygenase (CCD) in nanostructured films. CCD layers were alternated with poly(amidoamine) generation 4 (PAMAM G4) dendrimer using the electrostatic layer-by-layer (LbL) technique. Circular dichroism (CD) measurements indicated that the immobilized CCD preserved the same conformation as in solution. The thickness of the very first CCD layers in the LbL films was estimated at ca. 3.6 nm, as revealed by surface plasmon resonance (SPR). PAMAM/CCD 10-bilayer films were employed in detecting diluted catechol solutions using either an optical or electrical approach. Due to the mild immobilization conditions employed, especially regarding the pH and ionic strength of the dipping solutions, CCD remained active in the films for periods longer than 3 weeks. The optical detection comprised absorption experiments in which the formation of cis-cis muconic acid, resulting from the reaction between CCD and catechol, was monitored by measuring the absorbance at 260 nm after film immersion in catechol solutions. The electrical detection was carried out using LbL films deposited onto gold-interdigitated electrodes immersed in aqueous solutions at different catechol concentrations. Using impedance spectroscopy in a broad frequency range (1Hz-1kHz), we could detect catechol in solutions at concentrations as low as 10(-10) M. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: biosensor; layer-by-layer; enzyme immobilization; Cl-catechol 1,2-dioxygenase